USP39: a key regulator in malignant tumor progression - Li, Junyan; Zhong, Jinghua; Ye, Jianming; Xiang, Yi; Wang, Xiangcai (Frontiers in Oncology, 2025)
Ubiquitin-specific protease 39 (USP39), a member of the USP family, plays a unique role beyond classical deubiquitination by interacting with target molecules and regulating their pre-mRNA splicing, which enhances its functional specificity compared to other USP family members. Growing evidence highlights USP39’s critical involvement in the progression of malignant tumors, where it acts as a pro-tumor factor, influencing cancer growth, proliferation, and metastasis. This paper provides a comprehensive review of the structure and functional mechanisms of USP39, emphasizing its role in regulating malignant tumor progression across various cancer types. Additionally, we explore the potential for developing targeted inhibitors based on USP39’s regulatory functions, offering a theoretical framework for future drug development. Furthermore, the study examines USP39’s contribution to resistance against antitumor therapies, highlighting its clinical relevance in advancing cancer treatment strategies. Despite the advances made, research on USP39-specific inhibitors remains limited. This work introduces a novel approach to designing inhibitors by leveraging USP39’s functional and structural characteristics, paving the way for new therapeutic avenues in cancer research.